Trust in Online Peer-to-Peer Lending in Indonesia from a Cognitive-Based Perspective - Saraswati, Reni Mutiarani; Keung, Verrel; Putra, Fariz Hutama (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2024)
This study investigates the perceptions of peer-to-peer (P2P) lending intermediaries and borrowers on lender trust. The trust model was used to develop the lender's trust in the peer-to-peer (P2P) lending sector by incorporating a similar model from a previous study in China. There are three dimensions of cognitive-based trust used in this model, they are social capital, perceived risk and information quality. A partial least square regression structural equation modeling (PLS-SEM) was used to evaluate the model. A quantitative online survey was distributed to 100 P2P lenders in Jakarta, Indonesia. The data collected was analyzed using PLS-SEM for its convergent validity, reliability, discriminant validity, and model fit. This study's approach integrates the antecedents of trust points to identify the criteria of lenders for achieving a successful loan transaction. The findings of the study revealed that it is essential for borrowers to build a good reputation and provide sufficient information needed to boost a lender's trustworthiness.